A Live Bio-Therapeutic for Mastitis, Containing Lactococcus lactis DPC3147 With Comparable Efficacy to Antibiotic Treatment - Kitching, Michael; Mathur, Harsh; Flynn, James; Byrne, Noel; Dillon, Pat; Sayers, Riona; Rea, Mary C.; Hill, Colin; Ross, R. Paul (Frontiers in Microbiology, 2019)
Bovine mastitis is an ongoing significant concern in the dairy and agricultural industry resulting in substantial losses in milk production and revenue. Among the predominant etiological agents of bovine mastitis are Staphylococcus aureus, Streptococcus uberis, Streptococcus dysgalactiae and Escherichia coli. Currently, the treatment of choice for bovine mastitis involves the use of commercial therapeutic antibiotic formulations such as TerrexineTM, containing both kanamycin and cephalexin. Such antibiotics are regularly administered in more than one dose resulting in the withholding of milk for processing for a number of days. Here, we describe the optimisation of a formulation of Lactococcus lactis DPC3147 , that produces the two-component bacteriocin lacticin 3147, in a liquid paraffin-based emulsion (formulation hereafter designated ‘live bio-therapeutic’), with a view to treating cows with clinical/sub-clinical mastitis. Critically, in a field trial described here, this ‘ready-to-use’ emulsion containing live L. lactis DPC3147 cells exhibited comparable efficacy to TerrexineTM when used to treat mastitic cows. Furthermore, we found that the L. lactis cells within this emulsion were relatively stable for up to 5 weeks, when stored at 4°C, 22°C or 37°C. The relative ease and cost-effective nature of producing this ‘live bio-therapeutic’ formulation, in addition to its enhanced shelf life compared to previous aqueous-based formulations, indicate that this product could be a viable alternative therapeutic option for bovine mastitis. Moreover, the single-dose administration of this ‘live bio-therapeutic’ formulation is a further advantage, as it can expedite the return of the milk to the milk pool, in comparison to some commercial antibiotics. Overall, in this field trial, we show that the live bio-therapeutic formulation displayed a 47% cure rate compared to a 50% cure rate for a commercial antibiotic control, with respect to curing cows with clinical/sub-clinical mastitis. The study suggests that a larger field trial to further demonstrate efficacy is warranted.